IbM PEMBERDAYAAN PETANI JAMBU METE BERBASIS ENTREPRENEURSHIP - Muliadi, Agus (Jurnal Ilmiah IKIP Mataram, 2018)
The Farmer Group TUNAS MAJU is an organization founded in 2007 and serves to facilitate the cashew farming communities in North Lombok. Farmers only use cashew seeds for sale, while the cashew fruit is not used optimally by farmers, even wasted by useless as waste. Lack of knowledge of farmers become obstacles in managing the cashew fruit, but fruit can be processed into Nata de Mete. Therefore, IbM program is to empower people to cultivate Nata de Mete and Nata de Mete be further processed into a beverage packaging. IbM program has been carried out with the result of performance: (1) a site survey; (2) coordinate with the farmer group chairman TUNAS MAJU and Mangala Village Chief; (3) extension of cashew farmers conducted twice (4) Preparation of training the manufacture of Nata de Mete. (5) The training was conducted by three techniques, namely teaching; Demonstrations; Practice. (6) Assistance carried out by means of direct assistance and consultation. (7) The product produced in this training is Nata de Mete with characteristics that thickness Â± 08 to 1.8 cm; chewy texture; rather pale white color. Beverage Packaging While that feels good and fresh.